Assessment of Effectiveness and Side Effects of Subdermal Implant among User Women - Milal Mohammad Al Jeborry; Hanan Khudhair Hussein Al Kadhim; Suha J. Witwit (Medical Journal of Babylon)
Background:Implanon is a progestin-only implantable contraceptive; it offers promise, long-term, with a high-efficacy contraceptive. It is one of the most effective reversible contraceptives and is of the same effectiveness to sterilization. Objective:To assess the adverse effect profile and effectiveness of subdermal implants. Materials and Methods:A prospective study involved 48 women attending for insertion of the subdermal implant on days 2–5 of their cycle. The implant was inserted subdermally under the effect of local xylocaine of the nondominant arm. Results:The commonest side effect was weight gain constituted 62.5%. At the same time, amenorrhea was reported in 31.3%. Pain at the site of insertion constitutes 14.6%. While bleeding occurred in one case, which responded to local pressure. The commonest cause of discontinuation was weight gain constituted 12.5%. Followed by disturbances in the menstrual cycle. Discontinuation rate 41.7% (20 out of 48 cases). Conclusion:Implanon is an effective long-term contraception with few adverse effects.